Pengenalan Structural Equation Modeling dengan Lisrel dalam Olah Data Kuantitatif - Sugeng; Chelda Yuliana; Muhammad Yamin; Abd. Wahab Syahrani; Hasbi Sjamsir (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2023)
Processing data as a way to generate meaningful information to support accurate decision-making. Quantitative data processing training was conducted at SDN 004 Samarinda Ilir and SMA IT Granada Samarinda, attended by 13 S3 Education Management (MP) students, 8 S2 MP students, and elementary school teachers. Training materials include theory and continued practice of SEM analysis with LISREL. The results of the training showed that some participants successfully practised PRELIS analysis and continued LISREL investigation successfully, but some were still at the level of familiarity with the application. Based on feedback, participants gave